2019
DOI: 10.3390/medicina55040097
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Maneuver Investigation of Chasse Steps Among Male Elite Table Tennis Players

Abstract: Background and objectives: The popularity of table tennis has increased globally. As a result, the biomechanical movement patterns in the lower limb during table tennis have attracted extensive attention from coaches, scientists and athletes. The purpose of this study was to compare the differences between the long and short chasse steps in table tennis and evaluate risk factors related to injuries in the lower limb. Materials and Methods: Twelve male elite athletes performed forehand topspin strokes with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In all sports, there are risk factors for injury. Previous studies have shown that the rate of lower extremity injury was higher than the upper extremity, which is between 39-59% of the total injuries presented (lower extremity, upper extremity, and trunk injuries) (17). Table tennis is a sport characterized by small balls, high speed, a strong rotation, and many variations (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all sports, there are risk factors for injury. Previous studies have shown that the rate of lower extremity injury was higher than the upper extremity, which is between 39-59% of the total injuries presented (lower extremity, upper extremity, and trunk injuries) (17). Table tennis is a sport characterized by small balls, high speed, a strong rotation, and many variations (18).…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, the researchers also stated that there is a high percentage of pelvic (core) injuries (5.76%) due to the characteristics of sudden blocking movements in the game of table tennis. Strains and sprains are the most common types of injury in most sports, and also, the research shows that even due to the excessive hyperextension of the knee while the footwork of table tennis players (which is the most important element in table tennis) in short steps compared to long steps, the risk of an ACL injury may increase (17). However, probably due to the unilateral nature of table tennis and its effect on one side of the body muscles, and due to the core stability muscles, one-way muscle strengthening, neuromuscular and musculoskeletal balance, this eld generally has the highest number of people with TD (40%).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the definition of NA may differ across previous studies and thus may interfere with the validity of experimental data to a certain degree. 17 , 19 , 22 , 31 , 32 Future studies of table tennis footwork and differences between levels and/or genders using biomechanical methodologies must be done in order to fully understand the internal mechanisms of table tennis techniques that further enhance performance.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of kinetic energy, the biomechanics of lower limbs determine the level of swing performance through the kinematic chain pathway. 20 , 21 In recent years, some research studies have investigated the kinematic and kinetic characteristics of table tennis utilizing generic musculoskeletal models, comparing the differences between standing and squat serves in female table tennis athletes, 18 the effects of performance between the long and short chasse steps with table tennis forehand topspin strokes, 22 joint and plantar loading during cross-court topspin forehands with the footwork of cross step, one step and side step, 19 and comparison about lower-limb kinematics performing two different kind of forehand top spin: long-line and cross-court. 23 However, a reliable multi-segment musculoskeletal model of the foot was developed, which meets the researchers’ demands to provide an in-depth investigation of the internal mechanisms of the feet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation